2021
DOI: 10.5267/j.ac.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of attitudes, subjective norms and behavioral controls on the intention and corrupt behavior in public procurement: Fraud triangle and the planned behavior in management accounting

Abstract: This study explores the values that develop in society which are social constructs that are thought to be related to attitudes, norms, and controlling individual behavior in society and in turn can foster intentions and behavior to corrupt. This research was conducted empirically by involving 265 respondents from accountants, stakeholders, civil servants and inspectors in Central Java, Indonesia who were analyzed by Structural Equation Modeling (SEM) with AMOS analysis tools. The theoretical test results confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…To this end, the authors analyzed 265 respondents-including accountants, stakeholders, public officials, and inspectors in Central Java, Indonesia-by using structural equation modeling (SEM) with the AMOS analysis tools. In [42], the authors assessed the Fraud Triangle Theory and human behavior in order to study the factors of opportunity, financial processes, and rationalization. The authors emphasized the importance of psychological and moral aspects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the authors analyzed 265 respondents-including accountants, stakeholders, public officials, and inspectors in Central Java, Indonesia-by using structural equation modeling (SEM) with the AMOS analysis tools. In [42], the authors assessed the Fraud Triangle Theory and human behavior in order to study the factors of opportunity, financial processes, and rationalization. The authors emphasized the importance of psychological and moral aspects.…”
Section: Resultsmentioning
confidence: 99%
“…Refs. [40,42,43,47,54,58,61,62,64,66] failed to get any scores, which means that their title and abstract showed that they could answer the research question for this SLR, but after reviewing the full articles, no features related to fraud detection using machine learning techniques were discussed.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The Indonesian Anti-Corruption Agency (KPK) reported that 90% of corruption cases in the region are related to goods and services (Media Indonesia, 2021). Fraud that occurs in the government is generally carried out by o cials, people's representatives, and their partners (Zulaikha et al, 2021). One way to combat fraud is to prevent it (Albrecht et al, 2012).…”
Section: )mentioning
confidence: 99%
“…It was discovered that public sector officials fall short of efficiently carrying out their jobs and responsibilities. Due to the flaws in the procurement process that create numerous opportunities for procurement fraud to occur, procurement process violations and unlawful conduct may have an effect on the involvement of public sector officers in procurement fraud occurrences (Zulaikha et al, 2021). This research contributes to the body of knowledge by analysing the effects of the fraud triangle theory (i.e., pressure, opportunity, rationalisation) and workplace spirituality on procurement fraud occurrences among Malaysian public sector officials.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the 2018 analysis carried out by PwC found that public procurement in public sector increased from 19% in 2014 to 29% in 2018. Therefore, public procurement is claimed to be among the government activities that is most vulnerable to corruption and covers a wide range of illegal activities (Bernama, 2017;Zulaikha, Hadiprajitno, Rohman, & Handayani, 2021).…”
Section: Introductionmentioning
confidence: 99%